2021
DOI: 10.2217/pgs-2021-0131
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Barriers and Enablers of Pharmacogenomic Testing in Primary Care: A Qualitative Systematic Review with Meta-Aggregation Synthesis

Abstract: Introduction: Pharmacogenomic testing can indicate which drugs may have limited therapeutic action or lead to adverse effects, hence guiding rational and safe prescribing. However, in the UK and other countries, there are still significant barriers to implementation of testing in primary care. Objective: This systematic review presents the barriers and enablers to the implementation of pharmacogenomics in primary care setting. Materials & methods: MEDLINE, EMBASE, PsycINFO and CINAHL databases were searche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 59 publications
2
12
0
Order By: Relevance
“…A systematic review by Qureshi et al on the barriers and facilitators of pharmacogenetics in primary care suggested that implementation may be facilitated by educating clinicians around the benefits of pharmacogenetic testing. [31] A UK based study on perceptions of primary care clinicians revealed interesting concerns around the costeffectiveness of pharmacogenetics and the risks of direct-to-consumer consumer testing. [32] Reflecting on these findings as well as on the results from a structured review on implementation models by Hayward et al, it is clear that any pharmacogenetic programme in primary care must have an educational component as one of its core pillars in order to be successful.…”
Section: Implications For Clinical Practicementioning
confidence: 99%
“…A systematic review by Qureshi et al on the barriers and facilitators of pharmacogenetics in primary care suggested that implementation may be facilitated by educating clinicians around the benefits of pharmacogenetic testing. [31] A UK based study on perceptions of primary care clinicians revealed interesting concerns around the costeffectiveness of pharmacogenetics and the risks of direct-to-consumer consumer testing. [32] Reflecting on these findings as well as on the results from a structured review on implementation models by Hayward et al, it is clear that any pharmacogenetic programme in primary care must have an educational component as one of its core pillars in order to be successful.…”
Section: Implications For Clinical Practicementioning
confidence: 99%
“…The genes will be diagnosed and experimented and pharmacogenetic testing cannot be carried out unethically. According to the words of Qureshi et al (2021), the ethical considerations in the form of informed consent where the individual considered for this type of test needs to be informed to make the individual understand the relevance of the test and carry out that test effectively without any kind of prohibitions. The right towards information is another ethical aspect where the individual has the right to get every form of information regarding pharmacogenomic testing.…”
Section: Ethical Considerations For Pharmacogenomic Testingmentioning
confidence: 99%
“…, Fahim, et. al., 2023, Qureshi, et. al., 2021 Overcoming these challenges requires collaboration among stakeholders, including healthcare providers, researchers, policymakers, and patients, to develop guidelines, increase awareness, and ensure access to pharmacogenomic testing.…”
Section: Introductionmentioning
confidence: 99%